Genetic Variants of Abo Blood Group and Coronary Artery Disease - PK Chawla; CK Ponde; RM Rajani; AS Deshpande; RB Sawant; TF Ashavaid (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
Background: The ABO gene encodes for the blood group antigens which are expressed on the surface of RBCs, platelets and the vascular endothelium. Several recent studies and GWASs have identified ABO as a locus for thrombosis, myocardial infarction, and multiple cardiovascular risk biomarkers.  Objectives: The objective of the study was to determine the association of genetic variants in the ABO gene with coronary artery disease (CAD).  Study design-setting-patients: A total of 500 subjects including 250 angiographically verified CAD patients' age and gender matched with 250 angiographically verified controls were recruited for the study. Genotyping of variants A2 (deletion of C; rs918130198), B (G803C;rs8176747), O1 (deletion of G; rs8176719), O2 (G802A;rs1286157771) and A1 (wild type) alleles were performed by allele specific PCR and lipid profile, hsCRP & sICAM1 levels were estimated for all subjects.  Outcome measures: This study will help understand the influence of genetic variations in the ABO genotypes on the risk of CAD amongst Indians.  Findings & interpretation: Among the blood group alleles, O1 (Cases-32%; Controls-50%; p= 0.009) and the B allele (Cases-34%; Controls-19%; p=0.01) were significantly associated with CAD while others (A1, A2 and O2 alleles) were insignificant. The O1 allele suggested an atheroprotective role while the B variant was atherogenic. Genotypically, the BB genotype was more prone to develop CAD with a 5 fold increased risk while the O1O1 genotype was at least risk protecting the individual by 2 folds. The distributions of remaining genotypic combinations of blood groups were found similar in both the groups.  Conclusion: These findings suggest the B blood group individuals especially BB genotypes to be at higher risk for CAD while the O1 allele playing an atheroprotective role.